Intelligent cloud computing : first International Conference, ICC 2014, Muscat, Oman, February 24-26, 2014, Revised selected papers /: first International Conference, ICC 2014, Muscat, Oman, February 24-26, 2014, Revised selected papers. (2015) - Unknown
No abstract available